Influencias del estrés, ansiedad y depresión en el deseo sexual de estudiantes. Universidad Nacional de Chimborazo, 2021 - Aulestia Pillajo, María Cristina (2022)
Sexual desire is the motivation that drives the individual to participate in a sexual act where affective and cognitive processes intervene. Emotions are reactions influenced by previous experiences and physiological or behavioral elements. The research objective was to analyze sexual desire, stress, anxiety, and depression. Universidad Nacional de Chimborazo, 2021. It is a quantitative field study, with a cross-sectional, non-experimental design and descriptive level, with the participation of 150 students of the Medicine career. For data collection is used: The Sexual Inhibition Scale and the Depression, Anxiety, and Stress Scale (Dass-21). In the results of the research, it is evidenced that sexual desire, 46.7% of the sample is sexually inhibited against the risks of the coital act such as being discovered or contracting a sexually transmitted disease; Regarding emotions, 31.3% of the population presents anxiety symptoms of a moderate level, experiencing sensations of nervousness, tremors, tachycardia and breathing difficulties. Suppose you determine that the population is sexually inhibited and has mild anxiety. Based on the results, a psychological prevention plan was carried out with an integrative approach to provide techniques through which anxiety levels and various mood disorders can be managed to psych educate sexual desire, especially sexual inhibition.